Health inequities in mammography: A scoping review. Issue 160 (March 2023) - Chancellor, Matthew; Modi, Jay; Muhammad, Rohaan; Batioja, Kelsi; Garrett, Elizabeth; Waters, Philo; Vassar, Matt
Abstract: Objective: The objective of this scoping review is to chart the existing evidence on health inequities related to mammography and identify existing knowledge gaps to guide future research. Methods: This scoping review followed guidelines from the Joanna Briggs Institute and the PRISMA extension for scoping reviews. In July 2022, we searched PubMed and Ovid Embase for published articles on mammography screening, published between 2011 and 2021, written in English, and examining at least one health inequity as defined by the NIH. Screening and charting were both performed in a masked, duplicate manner. Frequencies of each health inequity examined were analyzed and main findings from each included study were summarized. Results: Following screening, our sample consisted of 128 studies. Our findings indicate that mammography screening was less likely in historically marginalized groups, patients who live in rural areas, and in women with low income status and education level. Significant research gaps were observed regarding the LGBTQ + community and sex and gender. No trends between inequities investigated over time were identified. Discussion: This scoping review highlights the gaps in inequities research regarding mammography, as well as the limited consensus across findings. To bridge existing research gaps, we recommend research into the following: 1) assessments of physician knowledge on the LGBTQ + community guidelines, 2) tools for health literacy, and 3) culturally competent screening models.